The experience on a sport centre pilot plant with solar assisted heat pump and a look forward for new control strategies and technology upgrade - Tagliafico Luca Antonio; Cavalletti Alessandro; Marafioti Chiara; Marchitto Annalisa (E3S Web of Conferences, 2021)
The pilot plant at the sport palace Palacus in Genoa is heated by a solar assisted heat pump, interfaced with a solar hybrid field and two integration gas burners. The heating system has been operating since 2012/13 and its performances have been collected almost continuously by means of a dedicated data acquisition system. The information and the experience acquired have been applied to the design of the revamping of the system, also considering the legislative changes occurred in Italy in the past decade, especially about photovoltaic production. The here presented case study allows the definition of some general design strategies to be implemented during the development of a new SAHP plant or when a revamping is required.